Educational Benefits of Kahoot! in Enhancing Skills: Investigating Students’ Perspectives - Nhan, Le Nguyen Ai; Trang, Kieu Thi Thu; Quyen, Nguyen Thi (VNU Journal of Science: Education Research; Vol 37 No 4DO - 10.25073/2588-1159/vnuer.4558, 2021)
This study focuses on exploring the contribution of Kahoot! to students’ skill enhancement. We set out to determine students’ perceived judgments on how much their skills have improved as a result of using Kahoot! inside classrooms. Deviating from several related research, we not only looked at the effects of playing Kahoot! games but also of creating Kahoot! games. Using a survey that takes Bloom’s taxonomy as its theoretical foundations, we elicited judgments from 95 university freshmen, sophomores, and juniors. Students’ self-reports were analyzed using a series of one-way repeated measures ANOVA, which reveals a number of interesting results. First, students reported significant skill improvement when they played Kahoot! during class and even more so when they themselves were involved in the creation of Kahoot! games. Second, not all of the examined skills are subject to the same degree of improvements, leaving some room for educators to ponder how they can use gamification to effectively develop students’ comprehensive skill set. Thirdly, freshmen and juniors reported the highest amount of skill improvements, indicating that certain game-based applications might be helpful for only certain groups of students. Taken together, we suggest that Kahoot! games can be utilized in classrooms for both knowledge enhancement and effective skill improvement.